Surprise as a Chronotopic Feature of the World in the Poem by F.I. Tyutchev Exists in the Autumnal Growing... - Anastasia A. Aksyonova (RUDN Journal of Studies in Literature and Journalism)
Today, the work of F.I. Tyutchev Exists in the Autumnal Growing , despite its textbookness, is devoid of a hermeneutical attitude towards it and is mainly used as a material for training schoolchildren in the search for metaphors, epithets, personifications, etc. The attitude of the reader from the standpoint of participatory thinking suggests something else - clarification of the artistic patterns of the depicted world. The article discusses the image of time and space through the prism of the surprise of the persona. Note that the world of the piece emphasizes wonder before things existent, as well as the fragmentation of time in order to slow down the process of showing (seeing). In the piece, the wonder of the persona contributes to the detail of the landscape. The proximity of the images of a spike and a web, a sickle and an idle trench serves as a representation of two aspects of human existence, where one symbolizes the material-bodied plane and hard work, and the other - the spiritual plane of existence, time, cyclicity, destiny. Comparison of the thread of the web with a human hair in the metaphor of “thinning and unbending, a web string” fits the image of a person into a detailed world order, introduces him to the unity of all that exists. The cyclicity of life is expressed by the harvest scene, which is not just the memories of the persona, but an indication of the upcoming transformation.